2014
DOI: 10.1186/1471-2164-15-895
|View full text |Cite
|
Sign up to set email alerts
|

New insights into domestication of carrot from root transcriptome analyses

Abstract: BackgroundUnderstanding the molecular basis of domestication can provide insights into the processes of rapid evolution and crop improvement. Here we demonstrated the processes of carrot domestication and identified genes under selection based on transcriptome analyses.ResultsThe root transcriptomes of widely differing cultivated and wild carrots were sequenced. A method accounting for sequencing errors was introduced to optimize SNP (single nucleotide polymorphism) discovery. 11,369 SNPs were identified. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…In contrast, western cultivars clearly separated from wild and eastern cultivated carrots, and some inbred lines (I3 and I4) have a purified genetic pattern shared with western cultivated accessions, reflecting the intensive breeding practiced in western regions. Nucleotide diversity (π) 25 estimates showed that wild carrots have a slightly higher level of genetic diversity than cultivated carrots (Supplementary Table 18), indicating the occurrence of a limited domestication bottleneck, consistent with previous findings 3,26 . When D. carota subspecies, which have morphological characteristics contributing to their sexual isolation relative to carrot 27 , were excluded from diversity estimates, this observation was more evident from comparative analysis (wild, π = 9.5 × 10 −4 versus cultivated, π = 8.6 × 10 −4 ).…”
Section: A R T I C L E Ssupporting
confidence: 89%
“…In contrast, western cultivars clearly separated from wild and eastern cultivated carrots, and some inbred lines (I3 and I4) have a purified genetic pattern shared with western cultivated accessions, reflecting the intensive breeding practiced in western regions. Nucleotide diversity (π) 25 estimates showed that wild carrots have a slightly higher level of genetic diversity than cultivated carrots (Supplementary Table 18), indicating the occurrence of a limited domestication bottleneck, consistent with previous findings 3,26 . When D. carota subspecies, which have morphological characteristics contributing to their sexual isolation relative to carrot 27 , were excluded from diversity estimates, this observation was more evident from comparative analysis (wild, π = 9.5 × 10 −4 versus cultivated, π = 8.6 × 10 −4 ).…”
Section: A R T I C L E Ssupporting
confidence: 89%
“…Future work will benefit from extra samples from neighboring countries of the central Asia geographic region. Rong et al [26] also used SNPs and samples of wild carrots from different geographic origins except central Asia, and their Bayesian tree showed that wild carrots from western Asia are the closest relatives to eastern cultivated carrots.…”
Section: Discussionmentioning
confidence: 99%
“…Arbizu et al [36], using 94 nuclear orthologs, also reported that accessions of D. carota from Portugal, Spain and Morocco were placed in an individual sub-clade with 100% bootstrap support. Rong et al [26] marked one group of their Bayesian tree containing subspecies of D. carota as “Mediterranean, southern Europe”. Within this group, there is a sub-clade consisting of samples from Portugal and Spain labeled subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes of carrot domestication were demonstrated, and genes under selection were identified based on transcriptome analyses (Rong et al, 2014). The processes of carrot domestication were demonstrated, and genes under selection were identified based on transcriptome analyses (Rong et al, 2014).…”
Section: Rootmentioning
confidence: 99%